The Eﬀects of Human Crowding and Store Messiness on Consumer Visit Intention: A Post Pandemic Study - Ali, Syed Muhammad Fauzan; Husseiny , Karamatullah; Adam, Aamir (JISR management and social sciences & economics, 2023)
Attraction towards decorated and tidy places is an innate human trait. The visit to well-organised places is more frequent whether for shopping or regular outings. This study aims to determine how environmental cues, such as human crowding and disorganised isles and shelves, inﬂuence the consumer intention to visit a departmental store in Pakistan in the post-covid era. The study investigates the mediating role of consumer-perceived contamination. The data was gathered from 298 participants in Karachi who frequently shopped at departmental stores. The collected data was analysed using PLS- SEM, and the results indicated that store messiness has a negative impact on consumer visit intention, which is mediated by perceived contamination. The results also showed that human crowding has a direct negative relationship with consumer visit intention, regardless of the consumer perceived contamination. It was suggested that managers should focus on enhancing the environment of the store to provide an exclusive shopping experience to the consumers and make use of strategies centered on improving environmental cues to mitigate the challenges associated with perceived contamination in the post- covid era.